Collective case study on healthy brand building: A qualitative investigation of brand building methods used by entrepreneurial ventures in Cape Town. - Levene, Sara (The IIE, 2016)
In a country such as South Africa, where unemployment is rife, entrepreneurship and entrepreneurial activity plays a vital role in assisting to boost the economy. However these entrepreneurial ventures face overwhelming odds in terms of actually surviving in this competitive and cutthroat context. The FNB/GIBSs report says that, "start-ups fail at a rate of about nine in ten in the first two years of operation" (Mafoyane, 2015). This study aims to delve into the branding aspect of these entrepreneurial ventures in Cape Town, South Africa. Branding is a crucial element of any business and is directly linked to the success of a business. This research aims to understand what methods are effective in branding an entrepreneurial venture in this specific context of Cape Town. This research is presented as a case study approach and three entrepreneurial ventures have been analysed, namely Skinny Scoop, Ucook and Nifty250. Each of these ventures started in 2014 and have been in operation for two years. Kevin Lane Keller’s seminal work regarding brand building and brand equity was used in this research in order to analyse if these brand-building methods were actually utilized in these three entrepreneurial ventures. In addition, Carmody, Cook, Enslin & Erwin’s (2010) healthy brand criteria were used in order to determine what methods of brand building contribute to creating a healthy brand. This research uncovered that Keller’s brand building model does indeed prove to have effective methods of creating a brand. This research highlights a strong alignment between Keller’s brand building steps and the entrepreneurial ventures being studied. In terms of a healthy brand, these methods do contribute to making a brand healthy. The data collected showed that Keller’s brand building steps does pave the way for these entrepreneurial ventures to grow and transform into healthy brands as compared to the healthy brand criteria. However, the one element of a healthy brand that seemed to present issues for these entrepreneurial ventures is the sustainability element. These three brands say that sustainability is a concern with the ever-changing market needs and macro environment of South Africa.
Keywords: Branding; Keller's brand building model